2021
DOI: 10.1108/ejim-05-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effects of team information processing on new product development success: revising the role of innovation orientation and team unlearning

Abstract: PurposeAlthough previous studies noted the importance for organizations in establishing an innovation strategy, few have examined innovation orientation as a multidimensional knowledge configuration. Therefore, this study draws on the valuable theoretical underpinnings of the resource-based view and information processing theory to examine the mechanism through which an organization's innovation orientation (IO) and team unlearning (TU) can impact new product development (NPD) success.Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…But some previous research has shown that there exists a conflicting association between this sort of malleability and project success. Malleability, for example, permits "mission drift" which counts against project success (Amaya et al, 2022;Edeh et al, 2020). One possible explanation for why we find a positive result is that the majority of our projects are research projects, and research is a context in which changes are welcomed, and even seen as a sign of success in themselves (if for example the change is through an unexpected finding which changes the orientation of the project).…”
Section: General Observationsmentioning
confidence: 84%
“…But some previous research has shown that there exists a conflicting association between this sort of malleability and project success. Malleability, for example, permits "mission drift" which counts against project success (Amaya et al, 2022;Edeh et al, 2020). One possible explanation for why we find a positive result is that the majority of our projects are research projects, and research is a context in which changes are welcomed, and even seen as a sign of success in themselves (if for example the change is through an unexpected finding which changes the orientation of the project).…”
Section: General Observationsmentioning
confidence: 84%
“…In a cross-sectional survey-study, Amaya et al (2022) found that team U/IF was an important precondition for success in NPDs, as they needed to handle vast amounts of information processed to generate new ideas. Based on the data of 255 NPD team members from 80 firms, U/IF showed its effect on teams’ information processing , which subsequently led to NPD success ( Amaya et al, 2022 ). The relationship between team unlearning and NPD success was fully mediated by team information processing.…”
Section: Resultsmentioning
confidence: 99%
“…In the community enterprises, the innovative process is lacking for the development of products and services. Previous study is also highlighted that innovative processes in NPD is most important (Amaya, Wu, & Liao, 2021). From the offer mentioned discussion, they study hypothesized that Hypothesis 4.…”
Section: Process For Product Developmentmentioning
confidence: 89%